2015
DOI: 10.1021/acsnano.5b00415
|View full text |Cite
|
Sign up to set email alerts
|

Dressing up Nanoparticles: A Membrane Wrap to Induce Formation of the Virological Synapse

Abstract: Next generation nanoparticle-based drug delivery systems require the ability to target specific organelles or subcellular regions in selected target cells. Human immunodeficiency virus type I (HIV-1) particles are evolutionarily optimized nanocarriers that have evolved to avoid intracellular degradation and achieve enrichment at the synapse between mature dendritic cells (mDCs) and T cells by subverting cellular trafficking mechanisms. This study demonstrates that integration of the glycosphingolipid, GM3, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 54 publications
1
35
0
6
Order By: Relevance
“…This GM3-specific segregation in mDCs has been observed before and was interpreted as a successful mimicry of GM3-mediated compartmentalization of the enveloped virus particles in deep peripheral membrane invaginations. 5,6 These differences can be exploited in the future for developing smart cell-specific delivery and drug release strategies.…”
Section: Resultsmentioning
confidence: 99%
“…This GM3-specific segregation in mDCs has been observed before and was interpreted as a successful mimicry of GM3-mediated compartmentalization of the enveloped virus particles in deep peripheral membrane invaginations. 5,6 These differences can be exploited in the future for developing smart cell-specific delivery and drug release strategies.…”
Section: Resultsmentioning
confidence: 99%
“…2d). We, therefore, also measured the caspase-3 levels obtained with high concentrations of lipid membrane wrapped NPs 55, 56 (MW-NP; initial membrane composition: 2% phosphatidylserine (PS), 58% dipalmitoylphosphatidylcholine (DPPC), 40% cholesterol). The membrane wrapped NPs remain stable even when incubated with cells in DMEM in the tens of nM concentration range.…”
Section: Resultsmentioning
confidence: 99%
“…Engagement of sialoadhesin CD169 (Siglec‐1) expressed on the surface of mDC with the ganglioside GM‐3 contained in the viral membrane triggers relocation to the cell periphery to initiate VS formation (Izquierdo‐Useros et al, ; Izquierdo‐Useros et al, ; Puryear et al, ; Puryear & Gummuluru, ; Puryear, Yu, Ramirez, Reinhard, & Gummuluru, ). It has been recently reported that the interaction of these molecules alone is enough to initiate VS formation (Yu et al, ). In DC, there is an enrichment of tetraspanins, actin, and ICAM‐1 at the contact site, whereas adhesion molecule LFA1 and HIV receptors CD4 CXCR4/CCR5 concentrate at the surface on the T‐cell side (Cavrois, Neidleman, Kreisberg, & Greene, ; Felts et al, ; Garcia et al, ; Geijtenbeek et al, ; Turville, Aravantinou, Stossel, Romani, & Robbiani, ; Yu, Reuter, & McDonald, ; Figure c).…”
Section: Virological Synapsementioning
confidence: 99%
“…Exploiting the mechanics of VS formation has led to the development of ganglioside GM3 membrane‐wrapped gold nanoparticles that were found to activate GM3‐CD169 trafficking pathway in mDC. The addition of GM3 to the virus‐like nanoparticles was enough to deliver the conjugate to CD81 + compartments that accumulated at the junction between mDC and T‐cells, resembling the structure of a VS (Yu et al, ). Another promising approach incorporates the delivery of CCR5 siRNA encapsulated in liposomes coated in antibodies against LFA‐1.…”
Section: Nanoparticles To Mimick Viruses: Potential Therapeutic Targets?mentioning
confidence: 99%